Mainstream nitrogen removal in membrane aerated biofilm reactor at minimal lumen pressure - Chen, Rongfen (2022)
Nitrogen removal via anammox is a promising and sustainable solution in mainstream wastewater treatment. To maintain stable anammox process, competitors of anammox bacteria should be suppressed while cooperators need to be favoured. This study demonstrated a synchronous aerobic and anaerobic ammonium removal process in a membrane aerated biofilm reactor (MABR) under minimal lumen pressure. By adjusting the lumen pressure, aerobic and anaerobic ammonium oxidation rate can be synchronized to minimize interference of nitrite oxidizing bacteria (NOB) by limiting NOB's access to both oxygen and nitrite. Long-term performance indicated that PN/A in MABR could be achieved at zero positive aeration pressure. Furthermore, by connecting two MABRs in series, high total nitrogen (TN) removal efficiency of 71.1% ± 5.3% was attained with a TN removal rate of 30.1 ± 3.2 mg-N/L/d. The organic carbon present in the wastewater reduced the nitrate concentration in the effluent while not affecting the overall nitrogen removal efficiency and rate. Real-time qPCR analysis suggested that the abundance of amoA gene was relatively stable while K-strategist Nitrospira 16S rRNA gene did not surge in the long-term operation. High throughput sequencing showed that Candidatus Brocadia and uncultured anaerobic ammonium oxidizing bacteria from Chloroflexi were the most abundant anammox taxa. Denitrifiers, such as Denitratisoma may be responsible to reduce the nitrate in the effluent.